2019
DOI: 10.18502/rmm.v7i1.5259
|View full text |Cite
|
Sign up to set email alerts
|

Acute Beetroot Juice Intake: Hematological, Antioxidant and Lipid Parameters in Female Athletes

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…In female soccer, BRJ consumption for 6 weeks was positively associated with improvement in haematological parameters related to red blood cell count and iron [50], but in another study where the same dose of BRJ was used but acutely, it did not show beneficial results in these haematological parameters [51]. In summary, the potential effect in women remains to be clearly established.…”
Section: Nitrate Consumption In Elite Soccermentioning
confidence: 95%
See 1 more Smart Citation
“…In female soccer, BRJ consumption for 6 weeks was positively associated with improvement in haematological parameters related to red blood cell count and iron [50], but in another study where the same dose of BRJ was used but acutely, it did not show beneficial results in these haematological parameters [51]. In summary, the potential effect in women remains to be clearly established.…”
Section: Nitrate Consumption In Elite Soccermentioning
confidence: 95%
“…Improvements in exercise economy and endurance capacity were also observed after consuming BRJ among healthy young adult males; however, no such benefits were seen in females [49]. Nitrates have also been studied, regarding their use in female athletes [50][51][52][53][54]. No ergogenic effects were observed on oxygen consumption, heart rate or aerobic time trial performance after the consumption of beetroot juice in female athletes [52,53].…”
Section: Nitrate Consumption In Elite Soccermentioning
confidence: 99%
“…Another significant feature of beetroot is that it meets 50-85% of dietary nitrate, thus increasing the content of nitrite and nitrate after consumption (Rg et al, 2018). With the highest nitrate and sugar content among natural foods, it has an increasing energy effect on athletes, and its importance is increasing daily (Lotfi et al, 2019). Studies have shown that beetroot has ergogenic effects.…”
Section: Beet and Beet Juicementioning
confidence: 99%
“…Amongst vegetables, beetroot is a remarkable source of nutrients as iron, nitrate, potassium, beta-alanine, sodium, folic acid, and magnesium. The advantages of consuming beetroot juice in human cases are, dealing with anemia, raising red blood cell numbers, increasing the oxygen-carrying capability of erythrocytes (RBCs), enlightening blood circulation, and make improvements to menstrual difficulties (Lotfi M, et al, 2019). On the other hand, a contrary impact of oral iron supplements negatively affects the treatment obedience and may lead to patients to withdraw from treatment.…”
Section: Introductionmentioning
confidence: 99%